A Structural Equation Modeling of the Relationship between Effective Communication, Motivation, Clear Vision and Efficiency Decision Making of the Leader Affecting the Commitment of Airline Business’s Employees in Thailand - Anunthawichak, Suang-I; Pinthapataya, Jutharat; Horpibulsuk, Nattira (Rajapark Journal, 2024)
The research aimed to develop and examine the relationship between effective communication, motivation, clear vision, and the efficiency of leaders’ decisions affecting the commitment of airline business employees in Thailand. The sample group used in this research included employees working in the airline business who received an operating license with definite flight routes within and abroad according to the Civil Aviation Authority of Thailand (CAAT) criteria. It consisted of employees from: Thai Airways, Bangkok Airways, Thai AirAsia, Thai Lion Air, Thai Vietjet Air, and Nok Air, totaling 400 people. The research tool was a questionnaire survey. Statistics used for data analysis included mean, standard deviation, and structural equation modeling. The results of the study were as follows: 1) The value χ2/DF = 1.135, P value = 0.52, GFI = 0.948, AGFI = 0.91, CFI = 0.996, RMR = 0.029, RMSEA = 0.018, TLI = 0.994. The determination of the model acceptability was interpreted according to the hypothesis set. 2) The structural equation model found that 2.1) Effective communication positively influenced motivation, clear vision, and efficiency decision-making; 2.2) Motivation positively influenced efficiency decision-making and employee’s commitment; 2.3) Clear vision positively influenced efficiency decision-making and employee’s commitment; and 2.4) Efficiency decision-making also positively influenced employee’s responsibility. The structural equation analyzed was reliable and can be used in practice. The structural equation of the relationship between effective communication, motivation, clear vision, and the efficiency of leaders’ decisions explained the impact on the commitment of airline business employees in Thailand at 76 percent (R2 = 0.76).